A History of God : The 4000-Year Quest for God - Armstrong, Karen (London Vintage Books, 1999)
The idea of a single devine being - God, Yahweh, Allah - has existed for over 4,000 years. But the history of God is also the history of human struggle. A controversial, extraordinary story of worship and war, A History of God confronts the most fundamental fact - or fiction - of our lives.
Include Index
Keywords: Islam--Doctrines -- Judaism--Doctrines -- God (Islam)--History of doctrines -- God--Biblical teaching